2011
DOI: 10.1074/jbc.m110.206532
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-associated Protein 1S (MAP1S) Bridges Autophagic Components with Microtubules and Mitochondria to Affect Autophagosomal Biogenesis and Degradation

Abstract: The ubiquitously distributed MAP1S is a homologue of the exclusively neuronal distributed microtubule-associated protein 1A and 1B (MAP1A/B). They give rise to multiple isoforms through similar post-translational modification. Isoforms of MAP1S have been implicated in microtubule dynamics and mitotic abnormalities and mitotic cell death. Here we show that ablation of the Map1s gene in mice caused reduction in the B-cell CLL/lymphoma 2 or xL (Bcl-2/xL) and cyclin-dependent kinase inhibitor 1B (P27) protein leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
172
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 114 publications
(177 citation statements)
references
References 48 publications
5
172
0
Order By: Relevance
“…MAP1S knockout mice were founded to be normal until 12 months old (Xie et al ., 2011a,b). GFP‐LC3 transgenic mice have been widely used as models for autophagy research (Kuma & Mizushima, 2007).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…MAP1S knockout mice were founded to be normal until 12 months old (Xie et al ., 2011a,b). GFP‐LC3 transgenic mice have been widely used as models for autophagy research (Kuma & Mizushima, 2007).…”
Section: Resultsmentioning
confidence: 97%
“…MAP1S enhances autophagy initiation through the LKB1‐AMPK‐mTOR pathway by sustaining the levels of Bcl‐2/XL and P27 (Xie et al ., 2011a; Liu et al ., 2012). We cultured MEFs developed from wild‐type and MAP1S −/− mice in the absence or presence of lysosomal inhibitor bafilomycin A1, and found that autophagy flux indicated by the increased levels of LC3‐II after treatment with bafilomycin A1 for the same time was dramatically reduced by the MAP1S depletion (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations